PENGARUH KELEMBABAN TERHADAP SIFAT OPTIK FILM GELATIN - Maddu, Akhiruddin; Modjahidin, Kun; Sardy, Sar; Zain, Hamdani (UI Scholars Hub, 2006)
Humidity Dependence of Optical Properties of Gelatin Films. Humidity dependence of optical properties of gelatin films prepared by casting technique has been investigated. Gelatin films was investigated its optical properties to varied humidity condition. Optical responses investigated are optical transmission and absorption at visible light spectrum measured utilizing a UV-Vis (Ultraviolet – Visible) spectrophotometer. The results of optical transmittance and absorbance obtained shows an optical response of gelatin films in widely visible light spectrum within range 530 – 680 nm, with most clearly response in a spectrum band in 580 – 650 nm. Different humidity treatment cause a significantly change of optical characteristics, that is the transmittance and absorbance change in to humidity. Transmittance of gelatin films increase with increasing humidity in a range 580 – 650 nm, in contrast with absorbance that is decrease with increasing humidity. Plot of transmission and absorption intensity with varied humidity from 37%RH to 99%RH at 610 nm exhibited a good linearity. Two samples showed same characteristics